Teknologi Augmented Reality pada Promosi Berbasis Android - Yuli Cahyaningsih (Journal of Computer Science and Engineering (JCSE), 2020)
Technological advances can be applied in the business world as a medium of promotional media. Augmented Reality (AR) is a technology that combines 2 dimensions and 3 dimensions into a ward, then projecting the virtual objects in real time. Augmented Reality can be utilized in a variety of needs, one of which is the utilization of promotional media on the Honda Genio brochure. The purpose of this research is to develop new interactive media in assisting the promotion media in Astra Motor Majenang with Android based Augmented Reality technology. The methods used are MDLC (Multimedia Development Life Cycle) consisting of six stages, the concept, the design, the material collecting, the assembly, testing, and the distribution (Distribuiton). The result of this research is an Android-based Augmented Reality promotional media app on the Honda Genio brochure that can display 3D motor objects and display specs in both text and audio form.  The conclusion of the study was from the test results Alpha Test system developed spared from disability or failure of use. As for test results Beta Test, 91.2% of respondents answered strongly agree that it shows that the Augmented Reality app as a promotional medium on Android-based Honda Genio brochure is very interesting and acceptable for users.